A synonymous mutation of rs1137070 cause the mice Maoa gene transcription and translation to decrease - Li, Kai Xin; Fan, Lei; Wang, Hongjuan; Tian, Yushan; Zhang, Sen; Hu, Qingyuan; Liu, Fanglin; Chen, Huan; Hou, Hongwei (Frontiers in Molecular Neuroscience, 2024)
The Monoamine Oxidase-A (MAOA) EcoRV polymorphism (rs1137070) is a unique synonymous mutation (c.1409 T > C) within the MAOA gene, which plays a crucial role in Maoa gene expression and function. This study aimed to explore the relationship between the mouse Maoa rs1137070 genotype and differences in MAOA gene expression. Mice carrying the CC genotype of rs1137070 exhibited a significantly lower Maoa expression level, with an odds ratio of 2.44 compared to the T carriers. Moreover, the wild-type TT genotype of MAOA demonstrated elevated mRNA expression and a longer half-life. We also delved into the significant expression and structural disparities among genotypes. Furthermore, it was evident that different aspartic acid synonymous codons within Maoa influenced both MAOA expression and enzyme activity, highlighting the association between rs1137070 and MAOA. To substantiate these findings, a dual-luciferase reporter assay confirmed that GAC was more efficient than GAT binding. Conversely, the synonymous mutation altered Maoa gene expression in individual mice. An RNA pull-down assay suggested that this alteration could impact the interaction with RNA-binding proteins. In summary, our results illustrate that synonymous mutations can indeed regulate the downregulation of gene expression, leading to changes in MAOA function and their potential association with neurological-related diseases.